NrdJ phylogeny - Daniel Lundin (Stockholm University, 2017)
Maximum likelihood phylogeny (RAxML; Stamatakis 2014) of representatives of 75% identity USEARCH clusters (Edgar 2010) of the full diversity of class II ribonucleotide reductases (NrdJ). Reliable positions in a Probcons (Do et al. 2005) alignment were selected with the BMGE algorithm using the BLOSUM30 matrix (Criscuolo & Gribaldo 2010) PROTGAMMAAUTO model.

The alignment is available in Seaview format (Gouy et al. 2010; http://doua.prabi.fr/software/seaview) with defined character sets for the different BMGE selections. The phylogenetic tree is available in nexml format that can be opened in Dendroscope (Huson et al. 2007; http://dendroscope.org/) and other tree viewers.
Keywords: 60102 Bioinformatics; Computational Biology; 60107 Enzymes; Evolutionary Biology; Evolutionary Biology; Evolutionsbiologi; Bioinformatics (Computational Biology); Bioinformatik (beräkningsbiologi); Bioinformatics and Computational Biology; Bioinformatik och beräkningsbiologi